2014
DOI: 10.1016/j.mrfmmm.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

New tool for biological dosimetry: Reevaluation and automation of the gold standard method following telomere and centromere staining

Abstract: The use of TC staining has permitted a reevaluation of the dose-response curve and the highly efficient automation of the scoring process, marking a new step in the management and follow-up of populations exposed to genotoxic agents including ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…23 . Image acquisition and analysis were performed using Isis software, (version 3.9.1, MetaSystems, version 3.9.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 . Image acquisition and analysis were performed using Isis software, (version 3.9.1, MetaSystems, version 3.9.1).…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that the introduction of telomere and centromere (TC) staining, using PNA probes, renders not only DC and centric ring (CR) scoring more efficient and robust, but also permits the detection of different types of ACs: ACs with four telomeres, resulting from a fusion event generally accompanying the formation of a DC or CR; ACs with two telomeres, representing terminal deletions; ACs without telomeres, representing interstitial deletions, as well as telomere deletions of the chromosome 2325 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we make use of the PCC-method in combination with PNA probes and the FISH technique in order to construct a dose response curve for up to 10 Gy. The usefulness, reliability and applicability of this approach in triage biodosimetry is compared with the conventional method through the scoring of dicentrics at metaphase, by means of Giemsa stain or the use of C/T PNA probes [23]. Furthermore, given that the application of the C/T PNA probes in combination with the FISH technique is inherently labor intensive and time consuming, a simple PCC-method, based on the scoring of Giemsa stained fragments in excess of 46, is also assessed and proposed here as an even more rapid alternative approach for triage biodosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of telomere and centromere staining not only renders the scoring of dicentric chromosomes and centric rings more reliable and robust but also permits the detection of different types of acentric chromosomes leading to the precise calculation of the number of DNA double-strand breaks (DSB). Manual scoring following TC staining in metaphase revealed a significantly higher frequency of dicentrics (p < 10 À3 ) (up to 30%) and estimated DSB (p < 10 À4 ) compared to uniform staining due to improved detection of unstable chromosomal aberrations leading to an improved dose response curve (M'Kacher et al 2014). The results of this intercomparison, illustrated in Figure 5 for the highest dose (3.27 Gy) whole body exposure sample, where the greatest variation is thus expected, confirm the accuracy of the DCA-TC methodology.…”
Section: The Aims Of This Inter-comparison Werementioning
confidence: 97%